Taking a Chance: A Formal Model of How Firms Use Risk in Strategic Interaction with Other Firms - Ross, David Gaddis (Academy of Management Review, 2014)
This article provides a formal mathematical treatment of the link between competitive advantage and risk in strategic interaction. In the first part of the analysis, I establish a basic mechanism whereby a rational, profit-maximizing firm that is risk neutral with respect to realized profits would nonetheless benefit from risk in the antecedent process of developing a competitive advantage. This result serves to motivate two game-theoretic models demonstrating that (1) the trade-off between risk and expectation in developing a competitive advantage and (2) the shape of this risk each define a different and previously unexplored dimension of differentiation along which firms choose distinctive competitive positions. Two other important aspects of market rivalry—the number of competing firms and their product market overlap—affect where firms position themselves and which firms have higher expected profit than others. The analysis offers a risk-based theory of the origins of competitive advantage among initially identical rival firms and sheds light on the empirical evidence regarding both the relationship between risk and profitability and the performance implications of corporate social responsibility.